Culture and Violence: An Anthropological Approach to Study Facets of Violence - Ana Banić Grubišić (Etnoantropološki Problemi, 2016)
Review of a book by Saša Nedeljkovic. Culture and Violence: An Anthropological Approach to Study Facets of Violence. 2011. Belgrade: Heir and the Department of Ethnology and Anthropology, University of Belgrade, p. 518